Bio-Green Synthesis of Bismuth Oxide Nanoparticles Using Almond Gum for Enhanced Photocatalytic Degradation of Water Pollutants and Biocompatibility - Radhalayam, D (Elsevier B.V., 2025)
The discharge of dye-contaminated industrial wastewater is a significant source of water and soil pollution. The eco-friendly synthesis of multifunctional bismuth oxide nanoparticles (BiO-NPs) offers a promising approach for the removal of toxic contaminants. The incorporation of natural polymers in nanoparticle production has gained significant scientific attention due to their environmentally friendly and efficient properties. This study emphasizes the use of almond gum (ALG) as a potent bio-reductant for the green synthesis of BiO-NPs. The synthesized BiO NPs exhibited a surface area of 24.5774 m2/g, demonstrating their potential for enhanced catalytic activity. The photocatalytic activity of the BiO NPs was evaluated by degrading Congo Red and Brilliant Green dyes under visible light irradiation, achieving degradation efficiencies of 90.21 % ± 0.32 and 90.52 % ± 0.29, respectively. Radical trapping experiments confirmed the primary roles of photo-generated electrons and hydroxyl radicals in the degradation process. The reusability analysis demonstrated that the BiO-NPs could be effectively recycled for 4 cycles, maintaining good stability. Degradation intermediates were identified using LCMS. Additionally, the catalytic reduction conversion of 4-nitrophenol to 4-aminophenol using NaBH₄ achieved a degradation efficiency of 92 % ± 0.41 within 32 min. Biocompatibility assessments using NIH/3T3 cell lines indicated that ALG-BiO NPs are safe for environmental applications. © 2025 Elsevier B.V.